Apoptosis in the Homeostasis of the Immune System and in Human Immune Mediated Diseases - Paganelli, R.; Giovannetti, A.; Pierdominici, M.; Iorio, A. D.; Cianci, R.; Murdaca, G.; Puppo, F.; Pandolfi, F. (Current Pharmaceutical Design, 2008)
The immune system has evolved sophisticate mechanisms controlling the development of responses to dangerous antigens while avoiding unnecessary attacks to innocuous, commensal or self antigens. The risk of autoimmunity is continuously checked and balanced against the risk of succumbing to exogenous infectious agents. It is therefore of paramount importance to understand the molecular events linking the breakdown of tolerance and the development of immunodeficiency. Apoptotic mechanisms are used to regulate the development of thymocytes, the shaping of T cell repertoire, its selection and the coordinate events leading to immune responses in the periphery. Moreover, they are at the heart of the homeostatic controls restoring T cell numbers and establishing T cell memory. T lymphocytes shift continuously from survival to death signals to ensure immune responsiveness without incurring in autoimmune damage. In this review we shall consider some key facts on the relationship of lymphopenia to autoreactivity, the mechanisms controlling positive and negative selection in the thymus, the role of apoptosis in selected primary immunodeficiency states and in systemic and organ-specific autoimmunity, with examples from human diseases and their animal models.
Keywords: selection